Massive Loss of Sulfur in HIV Infection - Breitkreutz, Raoul; Seitz, Stefanie Christine; Pittack, Nicole; Beichert, Matthias; Dröge, Wulf (Aids research and human retroviruses, 2000)
Skeletal muscle tissue from SIV-infected macaques was previously found to contain abnormally high sulfate and low glutathione levels indicative of an excessive cysteine catabolism. We now confirm the peripheral tissue as a site of massive cysteine catabolism in HIV infection and have determined the urinary loss of sulfur per time unit. The comparison of the sulfate concentrations of the arterial and venous blood from the lower extremities of 16 symptomatic HIV+ patients and 18 HIV- control subjects (study 1) revealed (1) that the peripheral tissue of HIV+ patients with or without highly active antiretroviral therapy (HAART) releases large amounts of sulfate and (2) that plasma sulfate, thioredoxin, and interleukin-6 levels are elevated in these patients. A complementary investigation of 64 asymptomatic HIV+ patients and 65 HIV- subjects (study 2) revealed increased plasma sulfate levels in the asymptomatic patients. The analysis of the daily urinary excretion of sulfate and urea of another group of 19 HIV+ patients and 22 healthy HIV- subjects (study 3) confirmed (1) that HIV+ patients experience a massive loss of sulfur and (2) that this loss is not ameliorated by HAART. The sulfur loss of asymptomatic patients was equivalent to a mean loss of about 10 g of cysteine per day. If extrapolated, this would correspond to an alarming negative balance of approximately 2 kg of cysteine per year under the assumption that the normal sulfate excretion equivalent to approximately 3 g of cysteine per day is balanced by a standard Western diet. The abnormally high sulfate/urea ratio suggests that this process drains largely the glutathione pool.
Gesehen am 03.02.2021